Towards an Islamic Enlightenment: The gülen Movement By M. Hakan Yavuz (New York: Oxford University Press, 2013. 320 pages.) (American Journal of Islam and Society, 2014)
M. Hakan Yavuz was one of the early contributors to the literature on theGülen movement, co-editing a major volume on the subject with John Espositoin 2003 (Hakan Yavuz and John Esposito, Turkish Islam and the SecularState: The Gülen Movement [Syracuse University Press: 2003]). In the interveningdecade the movement has grown considerably in size and influenceboth within Turkey and beyond, and has emerged as a major source of interestand apparently perennial controversy. Towards an Islamic Enlightenment istherefore a timely if ambitious book, for it sets out to provide a comprehensiveaccount of the movement. The author opens with an analysis of FethullahGülen’s theological teachings and then explores the movement’s structure andorganization, as well as its emergence and development in the context of Turkishsocial, religious, and political history. No other scholar has attempted sucha holistic analysis, for others tend to focus on just one of its many areas of influence,namely, education (Bekim Agai, Zwischen Netzwerk und Diskurs -Das Bildungsnetzwerk um Fethullah Gülen (geb. 1938): Die flexible Umsetzungmodernen islamischen Gedankengutes [EB-Verlag, 2004]), politics(Berna Turam, Between Islam and the State: The Politics of Engagement[Stanford University Press: 2007]), and economic enterprise (Joshua D. Hendrick,Gülen: The Ambiguous Politics of Market Islam in Turkey and the World[New York Press: 2013]).Yavuz lays out his thesis of “Islamic Enlightenment” in the introductionby drawing a paradigmatic distinction between the Muslim intellectual tradition’sliteralist/fundamentalists and modernist/reformists. He acknowledgesthe impact of Enlightenment ideas on the major thinkers in the latter category,but notes that those ideas have historically remained the preserve of the Muslimelite and never “penetrated the masses” (p. 6). According to Yavuz, the ...